Bilangan Kromatik Dari Graf Hasil Operasi Korona Pada Graf Bintang Dan Graf Ligkaran - Shindy Sagita Br Ginting; Mulyono Mulyono (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
Two graphs are operated with various operations, one of which is Operation Corona. The graphs that are operated in this paper are circle graphs and star graphs. Both graphs are operated with Operation Corona. The graph resulting from the operation is then colored using the Greedy Algorithm. The Chromatic Number obtained from the results of the Corona Operation on a graph (Cn ⊙ Sm) is χC_n⊙S_m = 3 for every m,n ≥ 3, {m,n ∈ N}. Because the graph resulting from the corona operation is non-commutative, the chromatic number obtained from the graph (Cn ⊙ Sm) is different from the graph (Sm ⊙ Cn). The chromatic number from the corona operation on the graph (Sm ⊙ Cn) is divided into 2, namely: χS_m⊙C_n = 3 for every odd n, and χS_m⊙C_n = 4 for every even n, m ≥ 3, n ≥ 4, {m, n ∈ N}.